Pengaruh Literasi Keuangan, Gaya Hidup dan Pendapatan Terhadap Pengelolaan Keuangan Keluarga Dengan Kontrol Diri Sebagai Variabel Moderasi pada Guru SMPN di Kecamatan Tewah - Jelly Beatrika; Usup Riassy Christa; Agustina Muliyani; Rita Sarlawa (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes the influence of financial literacy, lifestyle, and income on family financial management with self-control as a moderating variable among public junior high school teachers in Tewah District. A quantitative method was employed by collecting data through questionnaire distribution and analyzing it using SmartPLS 4.0. The results show that financial literacy, lifestyle, and income have a positive and significant effect on family financial management, and self-control moderates the effect of financial literacy, but does not moderate the effects of lifestyle and income. This conclusion highlights the importance of improving financial literacy and strengthening self-control to promote more effective and sustainable household financial management.